The prognostic value of changes in pulmonary vein flow patterns after surgical repair for primary mitral regurgitation - Yedidya, Idit; Stassen, Jan; Butcher, Steele; van Wijngaarden, Aniek L.; Wu, Yoska; van der Bijl; Pieter; Marsan, Nina Ajmone; Delgado, Victoria; Bax, Jeroen (Elsevier, 2025)
Background: The pulmonary vein (PV) flow pattern is influenced by the presence of mitral regurgitation (MR). After a successful reduction in MR severity, the pattern is expected to be changed. We aimed to evaluate the prognostic value of a change in the PV flow pattern in patients with primary MR undergoing mitral valve repair (MVR).
Methods: The PV flow pattern was assessed with transthoracic echocardiography in 216 patients (age 65 [IQR 56-72] years, 70% male) with primary MR before and after surgical MVR. The population was divided according to a change in the PV flow pattern following MVR into 'improvers' and 'non-improvers'.
Results: Non-improvers (15%) had a higher prevalence of paroxysmal AF at baseline (46% vs. 22%, p = 0.004), left ventricular dysfunction (LVEF ≤60%) (39% vs. 21%, p = 0.020), and had lower systolic pulmonary artery pressure (28[IQR 25-38] vs. 35[IQR 26-48] mmHg, p = 0.018) compared to improvers (85%). After a median follow-up of 83[IQR 43-140] months, 26(12%) patients died. Non-improvers had higher mortality rates than improvers (p = 0.009). On multivariable Cox regression analysis, a lack of improvement in the PV flow pattern remained independently associated with all-cause mortality (HR 2.322, 95% CI 1.140 to 4.729, P = 0.020).
Conclusion: A lack of improvement in the PV flow pattern is independently associated with worse long-term survival in patients with primary MR undergoing MVR.